Experimental research on transient radiation effects in microprocessors based on SPARC-V8 architecture. (November 2015) - Zhao 赵, Yuanfu 元富; Zheng 郑, Hongchao 宏超; Fan 范, Long 隆; Yue 岳, Suge 素格; Chen 陈, Maoxin 茂鑫; Du 杜, Shougang 守刚
Abstract: An experimental system is developed for the transient radiation effects testing of an anti-radiation hardened processor. Based on this system, the transient radiation effects in a microprocessor based on SPARC-V8 architecture was investigated. The dose-rate-soft-error index parameters of the processor were determined according to the test results, as were the influences on the function and timing parameters of the processor. The power supply balance is affected, which caused the system to reset and be the main source of soft errors. The results showed the circuit recovery time is primarily determined by the internal PLL, while the core power and the output-low-IO ports are more sensitive to the transient dose rate effect. The power-integrity-hardened design is proposed to mitigate the transient radiation effect.